The Borderland in the System of Contemporary International Relations: the Security Aspect - Nechaieva-Yuriichuk, Nataliia (My University, 2020)
The previous century brought to humanity many political trials. Nowadays, we witness new challenges to world security and stability. Besides, borderlands play a compelling role in the political processes of modernity. Some political actors, like the Russian Federation, try to keep and strengthen their influence at the expense of other states, including Ukraine. Therefore, a transformation of an aggressive policy of such players, from military to hybrid, provoke the surrounding world to think: what’s next?
Keywords: borderland, challenges, geopolitics, democracy